Study of irradiation effect of Xe+22 and Kr+14 ions on structural properties of Zn nanotubes. (23rd February 2018) - Zdorovets, M V; Kadyrzhanov, D B; Kenzhina, I E; Ivanov, I A; Kozlovskiy, A L
Abstract: The paper presents the results of synthesis and directed modification of structural properties of Zn nanotubes by irradiating with heavy ions. The nanotubes were obtained by electrochemical deposition in pores of template polymer matrices. It was established using SEM, XRD and EDS methods where irradiation with Xe +22 and Kr +14 ions makes it possible to modify the crystal structure of nanotubes. As a result of irradiation with Xe +22 ions, partial destruction of nanotubes is observed, which indicates an increase in the number of defects in the structure and a decrease in strength properties. Change in the crystal structure parameters is observed when irradiation with Kr +14 ions with fluence below 5  ×  10 11 ion cm −2 . That indicates the possibility of using Kr +14 ions for directional modification of nanostructures, while irradiation with Xe +22 ions leads to amorphization and destruction of nanotubes.